"Just war" theory: from Antiquty to Modertity - Пода, Т. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article is devoted to the historical and philosophical analysis of the "just war" theory from Antiquity to Modernity.